The association between anti-smoking legislation and prevalence of acute respiratory illnesses in Indian children - Mamta Verma; K. Sangeeta; Bhupendra Kumar Verma; Dharmendra Kumar Dubey; Mukul Mondal; Mousumi Nath Mazumder; Hafiz T.A. Khan; Vivek Verma (Elsevier, 2024)
Objective: Exposure to tobacco smoke causes numerous health problems in children, and create burden on the population in terms of economy, morbidity and mortality. In order to protect the child from exposure to tobacco smoke in the outdoor environment, sufficient legislative enactments are available in Indian legislation. The objective of the present study is to investigate the fact that in absence of any specific laws stating about protection of children from exposure to tobacco smoke in indoor environment, whether outdoor related legislations are sufficient to protect children from exposureand to explore the scope for enforcement of both state and central laws in improving health of children in India. Study design: The study considered cross-sectional survey data of Demographic and Health Survey Data on India, National Family and Health Survey fourth round (NFHS-4) for the year 2015-16 on Indian children (below age of four). Methods: Both bivariate and multivariate logistic regression models were used to assess the impact of anti-smoking laws on the prevalence of acute respiratory infection (ARI) based on the place of residence, indoor tobacco smoke exposure and age of the child. Results: The results have shown an inclination of ARI among children in association with states having single law, rural area resident, exposure to indoor tobacco smoke and age of the child, both as independent or in combination are quite conspicuous, and are found to be underestimated. The logistic regression also revealed the influence of these factors both as independent and even in interaction with other. Conclusions: Legislative intervention through both at central (or national)and state levels through anti-smoking laws will decrease the indoor tobacco smoke exposure as a result ARI prevalence will also decrease among children in India.